Implementation of The “Little Detective”: Structured Stimulation Programme to Improve Problem Solving Skills in Early Chilhood - Euis Trismayanti; Ati Nuriah; Atih Syaidah; Mira Sofatul Ma’la (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
This research is motivated by the low problem-solving abilities of early childhood children in Kober Cerdas Ceria 2, which is indicated by the high dependence of children on teachers and parents when facing simple problems. This research aims to improve children's problem-solving abilities through the